Effects of different plant root exudates and their organic acid components on chemotaxis, biofilm formation and colonization by beneficial rhizosphere-associated bacterial strains - Zhang, Nan; Wang, Dandan; Liu, Yunpeng; Li, Shuqing; Shen, Qirong; Zhang, Ruifu (Plant and soil, 2014)
Aim It is necessary to understand the roles of root exudates involved in plant-microbe interactions to inform practical application of beneficial rhizosphere microbial strains. Methods Colonization of Bacillus amyloliquefaciens SQR9 (isolated from cucumber rhizosphere) and Bacillus subtilis N11 (isolated from banana rhizosphere) of their original host was found to be more effective as compared to the colonization of the non-host plant. Organic acids in the root exudates of the two plants were identified by High performance liquid chromatography (HPLC). The chemotactic response and effects on biofilm formation were assessed for SQR9 and N11 in response to cucumber and banana root exudates, as well as their organic acids components. Results Citric acid detected exclusively in cucumber exudates could both attract SQR9 and induce its biofilm formation, whereas only chemotactic response but not biofilm formation was induced in N11. Fumarie acid that was only detected in banana root exudates revealed both significant roles on chemotaxis and biofilm formation of N11, while showing only effects on biofilm formation but not chemotaxis of SQR9. Conclusion The relationship between PGPR strain and root exudates components of its original host might contribute to preferential colonization. This study advances a clearer understanding of the mechanisms relevant to application of PGPR strains in agricultural production.